2017
DOI: 10.4269/ajtmh.16-0361
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Household Latrines and the Prevalence of Diarrhea in Idiofa, Democratic Republic of the Congo: A Cross-Sectional Study

Abstract: Abstract.Despite the importance of sanitation, few studies have assessed the effects of latrines on the health outcomes of children under 5 years of age. We assessed the relations between latrine coverage and the prevalence of diarrhea in children under 4 years of age. In this cross-sectional study, we analyzed the baseline data obtained as part of a longitudinal survey targeting 720 households in Idiofa, Bandundu, Democratic Republic of the Congo. We categorized latrines according to the presence of each majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
(14 reference statements)
1
12
0
Order By: Relevance
“…Children of household who had clean latrine or not faces seen around the pit or on the floor of latrine were three times less likely to develop diarrhea compared to children of household who had not clean latrine or faces seen around the pit of the latrine. This study is consistent with the study conducted in Idiofa, Democratic Republic of the Congo [17]. This explored that there is a strongly positive relationship of the presence of feces around the pit hole with the higher prevalence of diarrhea.…”
Section: Diarrhea N (%) Cor(95% Ci)supporting
confidence: 91%
“…Children of household who had clean latrine or not faces seen around the pit or on the floor of latrine were three times less likely to develop diarrhea compared to children of household who had not clean latrine or faces seen around the pit of the latrine. This study is consistent with the study conducted in Idiofa, Democratic Republic of the Congo [17]. This explored that there is a strongly positive relationship of the presence of feces around the pit hole with the higher prevalence of diarrhea.…”
Section: Diarrhea N (%) Cor(95% Ci)supporting
confidence: 91%
“…Observational studies conducted to evaluate the effects of interventions that prevent human feces from entering the environment have shown that they reduce diarrheal diseases and enteric parasite infections [ 10 – 15 ]. Most of those researches, however, have focused on the construction and utilization of household-level latrines.…”
Section: Introductionmentioning
confidence: 99%
“…That latrine is associated with significant improvements in health even when they do not fully meet the conditions of improved latrines. The effect of latrines on health parameters by demonstrating that latrines have correlations with health benefits regardless of whether they are improved [12]. Indiscriminate stools are a risk factor for diarrhea in infants when in direct contact with hands when the child is playing ground in the yard or behind the house or indirectly through vectors such as flies that land on the stool and are transmitted through food.…”
Section: Resultsmentioning
confidence: 99%
“…Diarrhea accounts for 1.8 million deaths in children in lowand middle-income countries (LMICs). One of the identified strategies to prevent diarrhea is handwashing [11], [12]. Knowledge about personal hygiene and waterborne diseases but the practice of personal hygiene activities has to be improved, especially the practice of handwashing.…”
Section: Resultsmentioning
confidence: 99%